(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Urinary tract infection is very common. Appropriate antibiotic is needed for effective treatment. The purpose of the study was to explore culture and sensitivity (Antibiogram) of common organism responsible for urinary tract infaction. Materials and methods: It was a descriptive study. Secondary data were randomly collected from Microbiology Department of a tertiary care hospital. Study period was July-September 2023. Due to resource constraint only 153 data sheets were randomly selected. Data were manually managed. ANOVA and Z test were used for validation of results. Results: A total of 153 reports were studied. Age range was 6months to 89 Years. Mean age 41 years and SD± 12. Highest frequency was 53(34%). It was among age group 15-45 years. Female preponderance was there 94(61%). Growth of organism was found is 72(47%) cases. Common organisms were Escherichia Coli 45(62%), Pseudomonas and Klebsiella were 08(11%) respectively. Staphylococcus aureus was 07(10%). For E. Coli, Nitrofurantoin, Meropenam and Amikacin were sensitive 42(93%) 40(89%) and 37(82%) respectively. Least sensitive were Cefixim and Cefuroxime. It was 08(18%) only. For Pseuodomonas Ceftazidime and Pipercillin were 07(88%) sensitive. Amikacin and Gentamycin were 05(63%) sensitive. Ciprofloxacin and Levofloxacin were 06(75%) sensitive. For Klebsiella Cotrimoxazole, Meropenam and Nitrofurantoin were 07(88%) sensitive. Least sensitive was Gentamycin 03(38%). For Staphylococcus Linezolid showed highest sensitivity 07(88%) and Ciprofloxacin and Cloxacillin showed 00% sensitive. For Enterococcus Amikacin and Gentamycin were 100% resistant. Others were 100% sensitive. Enterococcus showed 02(100%) sensitivity to Amoxyclav, Ciprofloxacin, Levofloxin, Linezolid, Meropenam, Nitrofurantoin and Vancomycine. Zero sensitivity shown to Amikacin, Gentomycin. Conclusion: Only 47% samples yielded growth of organisms. Commonest organisms were E. Coli. Pseudomonas & Klebsiella ranked second position. Staphylococcus aureus was third. There is variation in sensitivity pattern. So, culture sensitivity should be done before starting antibiotic. However Nitrofurantoin and Meropenam could be started empirically. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 106-110